2008
DOI: 10.1111/j.1572-0241.2008.01861.x
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Yogurt for the Treatment of Minimal Hepatic Encephalopathy

Abstract: This trial demonstrated a significant rate of MHE reversal and excellent adherence in cirrhotics after probiotic yogurt supplementation with potential for long-term adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
178
0
9

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(191 citation statements)
references
References 47 publications
4
178
0
9
Order By: Relevance
“…51 Bajaj et al further reported that probiotic yogurt treatment lead to a reversal of MHE in 71% of patients with non-alcoholic cirrhosis with no progression to OHE. 50 Consistent with prior findings, patients with MHE in this study had lower baseline HRQoL as determined by 36 item Short Form Health Survey (SF-36). However, probiotic treatment did not convey a significant difference from baseline HRQoL scores and this was likely related to the lack of sensitivity of the SF-36 in assessing HRQoL in patients with MHE.…”
Section: Probioticssupporting
confidence: 90%
See 1 more Smart Citation
“…51 Bajaj et al further reported that probiotic yogurt treatment lead to a reversal of MHE in 71% of patients with non-alcoholic cirrhosis with no progression to OHE. 50 Consistent with prior findings, patients with MHE in this study had lower baseline HRQoL as determined by 36 item Short Form Health Survey (SF-36). However, probiotic treatment did not convey a significant difference from baseline HRQoL scores and this was likely related to the lack of sensitivity of the SF-36 in assessing HRQoL in patients with MHE.…”
Section: Probioticssupporting
confidence: 90%
“…Probiotics are not only efficacious in the treatment of OHE, but demonstrate benefit for MHE. [50][51][52][53] In a placebo controlled trial, synbiotic treatment for 30 days resulted in a decrease in intestinal pH, blood ammonia levels, and reversal of MHE compared to placebo (50.0% vs 13.3%, respectively; P < 0.05). Moreover, none of the patients developed OHE in this study.…”
Section: Probioticsmentioning
confidence: 99%
“…123 Probiotics have also been shown to restore neutrophil phagocytic activity by lowering endogenous levels of IL-10 and TLR-4 expression in patients with cirrhosis. 124 However, in other studies no changes in the reduction of the plasma proinflammatory milieu 125 or outcomes have been demonstrated. 126 …”
Section: Probioticsmentioning
confidence: 95%
“…23 Ammonia also modulates glutamate neurotransmission and induces neurosteroid production in neurons, leading to a positive modulatory effect on the gamma-aminobutyric acid-A receptor. 24 Ammonia lowering therapies like lactulose, 11,25,26 rifaximin 27 and probiotics 28,29 have been shown to result in resolution of MHE and overt HE, thereby providing indirect evidence to ammonia's pathogenic role in HE. However, recent studies have shown the persistence of cognitive impairment in cirrhotics even after complete resolution of HE despite ammonia lowering therapy suggesting role of other factors.…”
Section: Pathogenesis Of Minimal Hepatic Encephalopathymentioning
confidence: 99%
“…49 Depression, anxiety-trait and alexithymic symptoms occurs in cirrhotics and are major determinants of impaired HRQOL. 50 Treatment of MHE with lactulose, 11 rifaximin 27,51 or probiotics 29 reverses MHE in majority of patients. Significantly HRQOL also improves with treatment of MHE.…”
Section: Effect Of Minimal Hepatic Encephalopathy On Quality Of Lifementioning
confidence: 99%